2019
DOI: 10.1007/s11255-019-02308-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trimetazidine on preventing contrast-induced nephropathy after cardiac catheterization

Abstract: Purpose Trimetazidine has been shown to prevent the risk of contrast-induced nephropathy (CIN) in patients with renal dysfunction undergoing percutaneous coronary intervention (PCI). However, the effect of trimetazidine on CIN in unselected patients is unknown. We aimed to evaluate the effect of trimetazidine on preventing CIN in unselected patients treated with PCI. Methods 2154 consecutive patients were enrolled and divided into the trimetazidine (n = 529) and non-trimetazidine group (n = 1625). Patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Importantly, most of the studies investigated these agents in combination with intravenous hydration. Despite positive result from monocentric study ( 115 ), the results were not replicated nor supported in adequately powered trials and meta-analyses ( 116 ). None of these additional pharmacologic preventions are currently widely accepted for CI-AKI prevention.…”
Section: Strategies To Prevent Contrast-induced Acute Kidney Injurymentioning
confidence: 92%
“…Importantly, most of the studies investigated these agents in combination with intravenous hydration. Despite positive result from monocentric study ( 115 ), the results were not replicated nor supported in adequately powered trials and meta-analyses ( 116 ). None of these additional pharmacologic preventions are currently widely accepted for CI-AKI prevention.…”
Section: Strategies To Prevent Contrast-induced Acute Kidney Injurymentioning
confidence: 92%
“…Meta-analysis by Ye et al included 6 studies targeting effect of trimetazidine in the prevention of CIN with total 377 patients in trimetazidine group and 387 patients in the control group receiving only IV isotonic saline hydration reported that Scr was significantly lower in trimetazidine group than control group 24 h and 48 h after contrast exposure, however, this difference was not significant on measuring Scr 72 h after contrast exposure [10]. This denotes the possibility of reaching a peak elevation of Scr before 72 h. Moreover, Onbasili et al in their study, showed significantly reduced incidence of CIN on measuring Scr 48 h after contrast exposure in patients with pre-existing chronic kidney disease who received trimetazidine before contrast exposure [11].However, a study of Lian et al failed to show a reduction in CIN in patients who received trimetazidine group (529 patients) versus the control group (1625 patients) taking into consideration that they used trimetazidine 20 mg three times per day starting 24 h before angiography [12]. Ibrahim et al in their study, added trimetazidine 35 mg twice daily 72 h before coronary angiography to isotonic saline hydration versus isotonic saline hydration only in patients with CrCl less than 90 ml/min undergoing elective coronary angiography and it showed a reduced incidence of CIN in trimetazidine group [13].…”
Section: Discussionmentioning
confidence: 95%
“…But the function of TMZ in preventing CIN in some clinical trials has shown conflicting results. Lian et al 24 reported a prospective randomized controlled study (529 patients with trimetazidine and 1,625 with hydration only) showing risk factors that were confounded after adjusting for potential, trimetazidine drug treatment was not relevant to CIN prevention. In contrast, in another research, 100 sufferers who underwent angiography, (50 patients with trimetazidine and 50 patients with hydration only) reported that the results of oral administration of twice daily oral 35 mg trimetazidine combined with standard early saline treatment has the function of stopping CIN in sufferers with kidney insufficiency.…”
Section: Discussionmentioning
confidence: 99%